COMPLAINT BEHAVIOR: RELATIONSHIPS INDIVIDUALISM, SELF CONFIDENCE AND VOICE INTENTION WITH GENDER AS MODERATING VARIABLE - Sri Hartini; Aventina Aventina (Journal of Economics, Business, and Accountancy Ventura, 2013)
The study aims to explain the customers’ complaint behavior. This especially attempts to reveal the relationships among antecedent variables ofcomplaint behavior. The study uses hypothetically quantitative design research toexplain relationships among variables. Due to the infinite number of population, accidental sampling technique is implemented. Path analysis and subgroup analysis were adopted to analyze the data. It was found that that customer’s individualism affect customer’s self confidence and gender was found tobe a moderating variable in the relationships. The customer’s self confidence influences the customer’s voice intention and gender was not moderating in this relationships. The customer’s individualism did not affect the voice intention and gender was found to be the moderating variable inthis relationship.